Repertoar bahasa masyarakat Cina di Aceh - Wildan, Wildan; Bahry, Rajab; Razali, Razali; Mawardi, Mawardi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
This study is about language repertoire of the Chinese community in Aceh. The aim of this study is to find out (1) the mastery of variety of languages and (2) the level of language mastery of the Chinese community in Aceh. This study is based on result of research in ten cities in Aceh. The data was collected by using questionnaire and interview method. The conclusion of this research are (1) the Chinese community in Aceh is included to a group of monolingual, bilingual, and multilingual community and mastery of many languages, such as Chinese, Indonesian, Acehnese, Bahasa Jamee, Javanese, Sundanese, Bataknese, English, Japanese, Korean, and Arabic; and (2) the level of their mastery toward the languages are varied.Their mastery of Indonesian (oral and written) is at the level ‘good’. Their mastery toward oral-Chinese is ‘good’, while written-Chinese is ‘fair’. Hereinafter, their mastery toward foreign language and vernacular be at the level ‘fair’.